(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article discusses the main scientific and methodological problems of training Greco-Roman style wrestlers. The author proposes a system for controlling the training process based on optimizing the parameters of technical actions and using special technical devices with feedback.